Influence of volume and surface conductivity on the transient surface charge characteristics of DC‐GIL insulator under thermal–electric coupled fields. Issue 8 (25th July 2022) - Li, Xiaolong; Han, Songling; Wang, Wen; Geng, Zhenxin; Lin, Xin
Abstract: Here, the transient surface charge distribution of a basin‐type insulator is investigated under thermal–electric coupled fields. Horizontally installed ±200 kV direct current gas‐insulated transmission lines (DC‐GIL) are employed, and a 3D geometric model is applied. An improved method is introduced in the transient simulation under coupled fields, which involves simplifying geometric model, decoupling calculation, applying weak form partial differential equation, and simplifying ion transport equation. The influence of volume and surface electric conductivity on the transient surface charge and electric field distribution is discussed. With increasing volume conductivity, the transient charge accumulation is accelerated due to the promotion of conduction through the insulator. With increasing volume conductivity, the polarity of the charge on convex surface changes from negative to positive, while it changes from positive to negative with increasing surface conductivity. This is the consequence of the transition in dominant conduction mechanism. Non‐monotonic variation of charge density is observed attributing to the variation transient field distribution. It can be concluded that the influence of volume and surface conductivity should be focused on when evaluating the insulation characteristics of DC‐GIL insulators, and the thermal gradient should be considered in dealing with the long‐term operating insulators.